Dampak Ekonomi Budidaya Belut (Anguilla Bicolor) Pada Masyarakat Lokal di Kabupaten Banyuwangi - Osmaleli Osmaleli (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Aquaculture in Indonesia has several superior commodities, one of which is eel. Eel (Anguilla bicolor) is a fish with high economic value and a type of fish that is an export commodity (Japan, Hong Kong, Germany, Italy, and several other countries). This condition is inversely proportional to the level of domestic eel consumption which is still relatively low. Aquaculture activities provide direct and indirect impacts on the local society, one of them is the economic impact of the existence of giant mottled eel aquaculture in the Banyuwangi District. The research aimed to analyze the economic impact of giant mottled eel aquaculture activities. The Survey research method was used and data were analyzed using descriptive and multiplier effect analysis. The research result of the economic impacts of giant mottled eel aquaculture that provides a positive economic impact on local society is indicated by the development of giant mottled eel aquaculture activities and the other sectors. Keynesian Local Income Multiplier value was 2.65. Type I Multiplier Income Ratio was 1.16 and Type II Multiplier Income Ratio was 1.6.